Asymmetric information within the corporate social responsibility market: impacts of signalling on consumer decisions - Moore, Natalie J. (2016)
This thesis consists of three papers on the economics of corporate social responsibility (CSR). The papers study different aspects of CSR from the perspectives of consumers and firms. The first paper looks at how consumers value CSR and their willingness to pay for ethical attributes in a product. We include a CSR signal to examine how information on CSR affects individuals’ preferences and willingness to pay. The second paper builds on the study in the first paper, however, we also include a CSR nudge and the Big Five Inventory on personality to examine the interaction between information and personality traits on the willingness to pay for CSR. Finally, in the third paper we look at how firms’ CSR signal can influence their financial performance.